Usage of blackboard and academic performance of university students: a partial least square approach - Chan, Tak Jie; Zhang, Dashu; Tengku Azzman, Tengku Siti Aisha (Raffles University, 2021)
Blackboard as a learning management system (LMS) is rarely used in Malaysian universities as it always seen as pricy. In addition, there is little research on blackboard usage among the students in Malaysia. Hence, this study adopted the Technology Acceptance Model (TAM) and aimed to determine the relationship between usage of blackboard (perceived ease of use, perceived usefulness) and students’ academic performance in one of the private universities in Petaling Jaya. A total of 100 valid responses were obtained. Researchers analyzed the data using Partial Least Square Structural Equation Modelling (Smart-PLS 3.2.7). The study found that perceived ease of use have a positive and significant relationship with students’ academic performance. However, there is no significant relationship between perceived usefulness and academic performance. The ramifications of this study to blackboard developers and university administrators are discussed; in terms of understanding how to improve academic performance through the usage of LMS and social networks site (SNS). Implications of the study, as well as suggestions for future studies are also discussed in this article.